Potret Preferensi Politik Pemilih Disabilitas pada Pemilihan Umum 2024 - Sahi, Yayan; Mahmud, Ramli; Tiara Kartika, Intan; Adjie, Zulfikar (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2025)
This study aims to analyze the political preferences of voters with disabilities in general elections and the determinants of their political preferences. This study used qualitative methods with a descriptive approach. Data collection techniques include observation, interviews, and documentation. Data analysis used an interactive model that includes data reduction, data presentation, and drawing conclusions or verification. The results of the study indicate that political preferences are born from values as a basis, perceptions are formed through direct experience and interaction with the political environment, and tendencies are reflected in participation patterns and satisfaction with democratic mechanisms. Political preferences of voters with disabilities are influenced by ideological values formed from educational background, social class, and religious affiliation. While group identity plays a role in strengthening solidarity, forming a sense of attachment, and directing political choices according to the common interest. Political preferences of voters with disabilities are not simply personal choices, but rather the result of the interaction between values, perceptions, and tendencies influenced by ideological values and group identity to strengthen political orientation.